2014
DOI: 10.1016/j.virol.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus-6B protein U19 contains a p53 BOX I homology motif for HDM2 binding and p53 stabilization

Abstract: In order to establish a successful infection, it is of crucial importance for invading viruses to alter the activities of the regulatory protein p53. Beta-herpesviruses stabilize p53 and likely direct its activities towards generation of a replication-friendly environment. We here study the mechanisms behind HHV-6B-induced stabilization and inactivation of p53. Stable transgene expression of the HHV-6B protein U19 was sufficient to achieve upregulation of p53. U19 bound directly to the p53-regulating protein H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Intriguingly, using the Rad51 RI-1 inhibitor (27), Wallaschek et al recently reported that the Rad51 recombinase is dispensable for HHV-6A and HHV-6B integration in U2OS cells (14). Our results also suggest that abrogation of the p53 protein, which is involved in DNA repair mechanisms and interacts with the HHV-6 U14 and U19 proteins (28,29), does not affect HHV-6 chromosomal integration. Thus, our results indicate that HHV-6 U94 and the cellular p53 and Rad51 proteins are dispensable for HHV-6 integration, suggesting that other viral or cellular recombinases can complement their functions.…”
Section: Discussionsupporting
confidence: 58%
“…Intriguingly, using the Rad51 RI-1 inhibitor (27), Wallaschek et al recently reported that the Rad51 recombinase is dispensable for HHV-6A and HHV-6B integration in U2OS cells (14). Our results also suggest that abrogation of the p53 protein, which is involved in DNA repair mechanisms and interacts with the HHV-6 U14 and U19 proteins (28,29), does not affect HHV-6 chromosomal integration. Thus, our results indicate that HHV-6 U94 and the cellular p53 and Rad51 proteins are dispensable for HHV-6 integration, suggesting that other viral or cellular recombinases can complement their functions.…”
Section: Discussionsupporting
confidence: 58%
“…The roles of many HHV-6 genes are poorly understood but like other herpesviruses, HHV-6 is able to circumvent the pathway that results in p53 mediated cell cycle arrest and so is able to replicate 12 . Several HHV-6 genes, including DR6/DR7 (ORF-1), U14 and U19, encode proteins that interact with p53 directly of indirectly 13 14 15 16 . Interestingly the U14 protein has been detected with p53 in virions and its role is under intense investigation 14 17 18 .…”
mentioning
confidence: 99%